Pro choice i pro life – rozbieżne dyskursy. Przyczynek do problemu debaty i konstruowania obiektywności - Paradowski, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Abortion has been a tool of birth control since time immemorial. The problem of abortion is as old as time itself. What has always made abortion a problem is the dilemma a woman faces due to her ability to procreate on the one hand, and the ‘liberation’ of woman from this dilemma – whether by denying her the right to abortion, or by forcing her to have an abortion – on the other. However significant and dramatic, a woman’s dilemma is not the subject of the present considerations. The subject refers to selected arguments intended to liberate woman from this dilemma, and the arguments used to confirm women’s competence with reference to the problem under discussion. The purpose is to demonstrate the principal differences of these two, arguments, as well as a narrower argument that might combine the intentions of both parties of this centuries-old debate.